The United States Containment Policy as a Defence Strategy During the Cold War:Korean War - Bennouh, Asma Zittouna Hamed, Bouchra (university of El-Oued, 2020)
During the cold war, the United States faced so many serious foreign policy issues; the most divisive one, of course, was the war in Korea. However, the overriding ambiguity of Asia's relation to the U.S. national interest was clouding the study of American policy in Asia. The Containment policy which was planned for Europe, was extended to Asia to cover the Korean War. Some studies on the evaluation of the United States Containment policy in Asia shows that it has created problems for the American-Asian relations rather than solving them. This research attempts to examine the American application of the containment policy throughout the Cold War era particularly during the American involvement in the Korean War between 1950-1953.The method adopted to achieve this purpose is the descriptivehistorical method which helps us describe the historical events of the U.S. interference Korea. The results of the study indicate that the ultimate goal of the United States of America was the prevention of the communist spread in the world under the policy of containment. The American administration employed several economic and political means to achieve the above aim in Europe. Nevertheless, the practice of the same policy was totally different in Asia. Thither, mainly in Korea, the Americans based on military forces to roll back the Soviet Union‟s Communism. Hence, the Korean War represents the turning point of the Containment policy. َ . نقذ َاجٍج انُلاياث انمخحذة الأمشيكيت خلال انحشب انباسدة انعذيذ مه قضايا انسياست انخاسجيت انخطيشة انقضايا إراسة نهجذنكاوج انحشب في كُسيا. َمع رنك ، فإن انغمُض انسائذ في علاقت آسيا بانمصانح انُطىيت نهُلاياث انمخحذة يزيذ مه غمُض دساست انسياست الأمشيكيت في آسيا. فقذ قامج امشيكا بخمذيذ سياست الاحخُاء انخي حمج صياغخٍا نخكُن مُجٍت نهذَل الأَسَبيت ، نخشمم آسيا نخغطيت انحشب انكُسيت ، َحظٍش بعط انذساساث حُل حقييم سياست الاحخُاء ا. وحاَل فيٍزا انبحذ دساست انخطبيق ٍ مه حه ً يت بذلا ُ ا خهقج مشاكم في انعلاقاث الأمشيكيت الآسي ٍ الأمشيكيت في آسيا أو -9151الأمشيكي نسياست الاحخُاء طُال حقبت انحشب انباسدة خاصت أرىاء انخُسط الأمشيكي في انحشب انكُسيت بيه . انطشيقت انمعخمذة نخحقيق ٌزا انغشض ٌي طشيقت َصفيت حاسيخيت حيذ حٍذف انذساست إنى َصف الأحذاد 9150 انخاسيخيت نهخذخم الأمشيكي في كُسيا. كما حشيش وخائج انذساست إنى أن انٍذف انىٍائي نهُلاياث انمخحذة الأمشيكيت كان مىع اوخشاس انشيُعيت في انعانم في ظم سياست الاحخُاء. اسخخذمج الإداسة الأمشيكيت انعذيذ مه انُسائم الاقخصاديت َانسياسيت نخحقيق ٌزا انٍذف في أَسَبا، غيش ان مماسست وفس انسياست الإحخُاءكاوج م . ا في آسيا َ خاصت في كُسيا ، ً خخهفت حمام فقذ مزهج انحشب انكُسيت وقطت ، حيذ اعخمذ الأمشيكيُن عهى انقُاث انعسكشيت نذحش شيُعيت الاححاد انسُفيخي. َعهيً ححُل في سياست الاحخُاء..
Keywords: The Cold War, Communism, Containment, The Korean War, The Soviet Union, The United States.